Building Access to Justice for Women as Victims of Prostitution as a Form of Guarantee of Human Rights - Kenny Sekar Arum Femia; Rosalia Dika Agustanti (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this study was to build access to justice for women who became commercial sex workers. The issue of women was chosen as a component in access to justice because of the existence of women as part of a disadvantaged group. The law as commander in chief in its enforcement involves law enforcement officers and in particular the government. Women as human beings whose rights are protected should be protected and respected regardless of their work. This study used the normative juridical method. The results of the study showed that actually women who became commercial sex workers were victims. The high cost of living and economic demands made a person accepting easily job offers and big salaries. So that when they enter the world of prostitution, there would be many cases of sexual violence experienced by commercial sex workers because users felt that they have paid and were free to do anything. That in fact the form of legal protection in the context of guaranteeing human rights has existed in several laws and regulations. However, we know that its implementation is not easy, so cooperation between institutions and law enforcement officers is needed so that the legal objectives of justice, certainty and benefit can be realized